On the 1/f Spectrum in Slow Solar Wind Turbulence: The Role of Alfvénicity - Mason Dorseth; Sofiane Bourouaine; Jean C. Perez (The Astrophysical Journal Letters, 2024)
The slow solar wind has been recently observed to have a number of intervals that are dominated by large-scale Alfvénic fluctuations, especially within 1 au, with similar turbulence characteristics to those found in fast wind streams, including a 1/ f range. These results suggest that the slow solar wind exists in at least two flavors: the typical slow wind that generally does not exhibit a 1/ f range and an Alfvénic wind that is more similar to fast wind streams. The Alfvénic slow wind is usually differentiated from the typical slow wind (not dominated by Alfvénic fluctuations) by the normalized cross helicity, σ _c . Values of ∣ σ _c ∣ near unity are associated with Alfvénic fluctuations, whereas values near zero are typically thought of as non-Alfvénic. This classification by cross helicity excludes the case of solar wind fluctuations dominated by balanced Alfvénic turbulence, i.e., the turbulence regime where there is equal energy flux of counterpropagating fluctuations propagating along the mean field. We use a large statistical analysis to isolate intervals of slow wind at 1 au in a 20 yr period of Wind data. These intervals are sorted into subsets corresponding to the type of slow wind via the mean values of their magnetic compressibility and cross helicity. Our analysis finds several intervals of low-cross-helicity slow wind dominated by balanced Alfvénic turbulence, which possess similar characteristics found in high-cross-helicity streams. Our results support the conclusion that a 1/ f spectrum may be a property associated with streams dominated by Alfvénic turbulence, whether the turbulence is balanced or imbalanced.